IDIOMS WITH A FLORAL COMPONENT AND DIFFICULTIES OF THEIR TRANSLATION - Mukhammadiyeva Shokhsanam Mansur daughter (American Journals Publishing, 2023)
This article is devoted to the study of English idioms with flora component, their meaning and use in speech. The aim of the work is to define the concept of "idioms", the history of idioms with the component of flora, centuries-old human observations of the world of flora and the attitude of people to this area of reality. The article also reveals the peculiarities of English idioms with flora component important for translation and considers the problem of adequacy and equivalence in translation, as well as the ways of translation of English idioms into Uzbek.
Keywords: component; idiomatic structure; linguistic and semantic independence; classification; equivalent.